Copolymers of N-(4-bromophenyl)-2-methacrylamide with 2-hydroxyethyl methacrylate (eXPRESS Polymer Letters)
The radical-initiated copolymerization of N-(4-bromophenyl)-2-methacrylamide (BrPMAAm) with 2-hydroxyethylmethacrylate (HEMA) was carried out in 1,4-dioxane solution at 70°C using 2,2’-azobisisobutyronitrile (AIBN) as an initiator with different monomer-to-monomer ratios in the feed. The copolymers were characterized by FTIR, 1H- and 13C-NMR spectral studies. Gel permeation chromatography was employed for estimating the weight average (Mw) and number average (Mn) molecular weights and polydispersity index (PDI) of the copolymers. The copolymer composition was evaluated by nitrogen content (N for BrPMAAm-units) in polymers, which allowed the determination of reactivity ratios. Monomer reactivity ratios for BrPMAAm (M1)-HEMA (M2) pair were determined by the application of conventional linearization methods such as Fineman-Ross (F-R), Kelen-Tüdõs (KT) and Extended Kelen-Tüdõs (EKT) and a nonlinear error invariable model method using a computer program RREVM. The characterizations were done thermogravimetric analysis (TGA). The antimicrobial effects of polymers were also tested on various bacteria, and yeast.